Public library and local mobile web content - Juárez-Urquijo, Fernando (Anuario ThinkEPI, 2012)
Web 2.0 convergence with the mobile web is shifting the very nature of the Internet. Local multimedia holdings generated in a mobile-networked society often don´t fit with library catalogs. Their methods of diffusion and discovery move away from those associated with the traditional library and into social networking and new devices. Local archive-building in this new context requires content fitted to the new devices, skilled people to interact with them, and libraries that understand new forms of information demand and consumption. In order to find its place in this context, the library must combine its traditional role as a dynamic agent specialized in providing access to bibliographic resources with a new role as an advocate for informal web content.
Keywords: Public library; Local memory; Local content; Mobile web; Mobility.